Case Report: Identification of a novel STAT3 mutation in EBV-positive inflammatory follicular dendritic cell sarcoma - Ramsey, Megan C.; Sabatini, Peter J. B.; Watson, Geoffrey; Chawla, Tanya; Ko, Michael; Sakhdari, Ali (Frontiers in Oncology, 2023)
EBV-positive inflammatory follicular dendritic cell sarcoma (EBV+ IFDCS) is an uncommon disease primarily observed in Asia. It is characterized by the development of tumors believed to originate from follicular dendritic cells (FDC). The consistent association between this condition and clonal EBV infection suggests EBV's involvement as an etiological factor. However, diagnosing EBV+ IFDCS can be challenging due to its morphological variability and diverse immunohistochemical staining patterns. The genetic characteristics of EBV+ IFDCS remain insufficiently understood. To address this knowledge gap, we present a case study of a 47-year-old male patient diagnosed with EBV+ IFDCS. We utilized a Next-generation sequencing (NGS) platform to investigate the genetic profile of the tumor cells. We identified a single pathogenic mutation (G618R) in the STAT3 gene. This finding provides valuable insights into the genetic alterations associated with EBV+ IFDCS and potentially contributes to our understanding of the disease's pathogenesis.